PENGARUH PENGUMUMAN DIVIDEN TERHADAP HARGA SAHAM DAN ABNORMAL RETURN PADA INDUSTRI JASA DI BURSA EFEK INDONESIA - BELLA YONATAN, CARISSA (Fakultas Ekonomi Universitas Tadulako, 2016)
The aim of this study is to determine the influence of dividend announcement on stock prices and abnormal return in the services industries listed on Indonesia Stock Exchange. This study is descriptive-quantitative. The research methods used are simple linear regression and paired T-test or Two sample T-test for comparing the two means. The result of the first hypothesis that is dividend increases variable shows significant influence on stock prices with the value of t-count is 2.876 > the value of t-table 1.667 and dividends decreases with t-count value of 0.858 < the value of t-table 1.696, proves the second hypothesis shows no significant influence on stock prices. Then the third hypothesis which states that dividend increases influence the abnormal return before and after the dividend announcement has t-count value of 7.22 > t-table is 2.776; and the fourth hypothesis that states that dividend decreases the abnormal return before and after dividend announcement showd t-count 0.416< t-table 2.776. This indicates that the fourth hypothesis in this study has no significant influence.